Exchange : 26 artists from Düsseldorf - 25 artissts from Reading. - Städtische (Keller)galerie Düsseldorf, Düsseldorf; Museum and Art Gallery, Reading (Düsseldorf : Städtische (Keller)galerie Düsseldorf, 1983)
Abs, Elisabeth ; Armborst, Hanns ; Armborst-Wimmershoff, Annette ; Beckert, Jutta ; Berke, Sybille ; Bräuer, Reinhold ; Bugdahn, Udo ; Dobloug, Jorgen ; Dünnbier, Hildegard ; Ehrlich, Nora ; etc.
Exchange : 26 artists from Düsseldorf - 25 artissts from Reading / 25 Künstler aus Reading - 26 Künstler aus Düsseldorf, Städtische (Keller)galerie, Düsseldorf / Museum and Art Gallery, Reading, 24 August to 18 September 1983
boek